2013
DOI: 10.1093/hmg/ddt426
|View full text |Cite
|
Sign up to set email alerts
|

A novel estrogen receptor-microRNA 190a-PAR-1-pathway regulates breast cancer progression, a finding initially suggested by genome-wide analysis of loci associated with lymph-node metastasis

Abstract: To identify microRNAs that are important in regulating breast cancer progression, the present study used data for the 199 961 single-nucleotide polymorphisms (SNPs) in 837 breast cancer patients genotyped in a recent genome-wide association study to identify loci associated with lymph node metastasis (LNM). SNPs tagging the 15q22.2 locus showed a significant association with LNM and miR-190a was found to be the only microRNA in this region. The role of miR-190a in LNM was supported by the findings that increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 53 publications
1
37
0
Order By: Relevance
“…This result provides strong evidence for us to further explore the role of ceRNA regulatory networks in LN metastasis. In a previous study [37], miR190 was found to be the only miRNA identified by a genome-wide association study in the loci associated with LN metastasis of breast cancer. Our findings support the notion that miR190 functions as a metastasis suppressor, significantly reducing invasiveness, migration and lymphangiogenesis by regulating LNMICC expression.…”
Section: Discussionmentioning
confidence: 92%
“…This result provides strong evidence for us to further explore the role of ceRNA regulatory networks in LN metastasis. In a previous study [37], miR190 was found to be the only miRNA identified by a genome-wide association study in the loci associated with LN metastasis of breast cancer. Our findings support the notion that miR190 functions as a metastasis suppressor, significantly reducing invasiveness, migration and lymphangiogenesis by regulating LNMICC expression.…”
Section: Discussionmentioning
confidence: 92%
“…In breast cancer, overexpression of miR-190a has inhibited the cell migration and invasiveness. Moreover, miR-190a expression in primary breast carcinomas correlated with overall survival [29]. Nevertheless, the role of miR-190a in breast cancer biology is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies have linked oestrogen-induced deregulation of miRNA with phenotypic changes that contribute to breast carcinogenesis (Castellano et al, 2009;Chu et al, 2014;Pinho et al, 2013). Consequently, it is possible that aberrant miRNA expression induced by activation of ERα by PhIP could be an important factor in the carcinogenesis induced by the chemical.…”
Section: Introductionmentioning
confidence: 99%